Lateralized evoked responses in parietal cortex demonstrate visual short-term memory deficits in first-episode schizophrenia. (November 2020) - Coffman, Brian A.; Murphy, Tim K.; Haas, Gretchen; Olson, Carl; Cho, Raymond; Ghuman, Avniel Singh; Salisbury, Dean F.
Abstract: Working memory dysfunction may be central to neurocognitive deficits in schizophrenia. Maintenance of visual information in working memory, or visual short-term memory (vSTM), is linked to general cognitive dysfunction and predicts functional outcome. Lateralized change-detection tasks afford investigation of the contralateral delay activity (CDA), a useful tool for investigating vSTM dysfunction. Previous work suggests "hyperfocusing" of attention in schizophrenia, such that CDA is increased when a single item is maintained in vSTM but reduced for multiple items. If observed early in the disease, vSTM dysfunction may be a key feature of schizophrenia or target for intervention. We investigated CDA during lateralized vSTM of one versus three items using sensor-level electroencephalography and source-level magnetoencephalography in 26 individuals at their first episode of schizophrenia-spectrum psychosis (FESz) and 26 matched healthy controls. FESz were unable to modulate CDA with increased memory load – high-load CDA was reduced and low-load CDA was increased compared to controls. Further, sources of CDA in posterior parietal cortex were reduced in FESz and indices of working memory were correlated with neurocognitive deficits and symptom severity. These results support working memory maintenance dysfunction as a central and early component to the disorder. Targeted intervention focusing on vSTM deficits may be warranted to alleviate downstream effects of this disability.